If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (35 + -2x)(70 + -2x) = 0 Multiply (35 + -2x) * (70 + -2x) (35(70 + -2x) + -2x * (70 + -2x)) = 0 ((70 * 35 + -2x * 35) + -2x * (70 + -2x)) = 0 ((2450 + -70x) + -2x * (70 + -2x)) = 0 (2450 + -70x + (70 * -2x + -2x * -2x)) = 0 (2450 + -70x + (-140x + 4x2)) = 0 Combine like terms: -70x + -140x = -210x (2450 + -210x + 4x2) = 0 Solving 2450 + -210x + 4x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(1225 + -105x + 2x2) = 0 Factor a trinomial. 2((35 + -2x)(35 + -1x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(35 + -2x)' equal to zero and attempt to solve: Simplifying 35 + -2x = 0 Solving 35 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + -2x = 0 + -35 Combine like terms: 35 + -35 = 0 0 + -2x = 0 + -35 -2x = 0 + -35 Combine like terms: 0 + -35 = -35 -2x = -35 Divide each side by '-2'. x = 17.5 Simplifying x = 17.5Subproblem 2
Set the factor '(35 + -1x)' equal to zero and attempt to solve: Simplifying 35 + -1x = 0 Solving 35 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + -1x = 0 + -35 Combine like terms: 35 + -35 = 0 0 + -1x = 0 + -35 -1x = 0 + -35 Combine like terms: 0 + -35 = -35 -1x = -35 Divide each side by '-1'. x = 35 Simplifying x = 35Solution
x = {17.5, 35}
| Y^2=2px+p^2 | | 13x+2=13x-4 | | (x-b)=x | | 2x-5/7=8/25 | | x+(-16)=-12 | | nx=3y-5 | | 2/3(m-8)=9 | | 35=3x+2(x-5) | | 24000/X=0 | | 0.2x-3.4=0.5x-2.5 | | 6=1-3p | | 130=24x+2 | | 18x-6=120 | | 6=1-3p+2 | | 5x-2=2(5x+1)-1 | | 3(18-2^3)/2 | | P=7/100q-250 | | Y=X^4-6x^2+12 | | 6-7x-2=-17+4x-12 | | 3(2x+7)=3x-30 | | 18y+7=29 | | 19=5y+24 | | (27/9)^2-6 | | 35x+1=36x-1 | | -100/-20 | | 20x-8=18x+6 | | w^4-9w^2+8=0 | | (2x+7)4=124 | | B+2+3=7 | | 20x-2=18x+8 | | -3x+7=1-3x | | 0.7(x+9)=15 |